Outlawed : between security and rights in a Bolivian city - Goldstein, Daniel M., 1965- (John Hope Franklin Center book., 2012)
An ethnography examining how indigenous residents of crime-ridden, marginalized neighborhoods in Cochabamba, Bolivia, struggle to balance human rights with their need for safety and security.